Inventarisasi Potensi Tanaman MPTS (Multipurpose Tree Species) dan Pemanfaatannya di Kawasan HKm Buttu Puang Kabupaten Polewali Mandar - Idris, Andi Irmayanti; Aulia, Nudia; Irundu, Daud (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2024)
MPTS (Multipurpose Tree Species) plants are plants that have various benefits or functions that can be used for various purposes, usually MPTS plants have more than one function such as wood and non-wood production, soil and water conservation, as well as contributing to social welfare by providing goods and services needed by society, such as food, medicine and traditional industrial raw materials. This plant is planted in various lands including community forests. This research aims to determine the types and index of the importance of MPTS (Multipurpose Tree Species) plants and their use in the Buttu Puang Forest Area. The method used in this research is a quantitative method by calculating an important value index based on established criteria. The results of the research found 14 types of plants, namely Local Durian, Alle Durian, Montong Durian, Garuda Rambutan, Longan Rambutan, Cocoa, Robusta Coffee, Local Langsat, Forest Mango, Clove, Palm Sugar, Avocado, Jackfruit, and Breadfruit. Cocoa plants are the most dominant plants with the highest INP, 81.69, and avocado plants with the lowest INP, 2.85. The interview results show that the most profitable MPTS crops are cocoa and sugar palm. Keywords: Inventory, Potential, MPTS Plants, Utilization